Pendampingan Perancangan Sistem Informasi Akuntansi Terintegrasi untuk Meningkatkan Efisiensi Operasional dan Pengendalian Internal pada UMKM PetDiary - Nabila Safitri Nurrahmah; Risma Handayani; Wina Alya Fahmitha; Ridwan Taufik; Eva Patricia Gianni Christy; Melania Lintang Kenisah (LPPI UMN AL WASHLIYAH, 2026)
This community service activity aims to analyze and design an integrated accounting information system for PetDiary, an MSME currently relying on semi-manual recording. The implementation methods included direct observation, in-depth interviews with the owner, and a comprehensive system analysis using the PIECES framework (Performance, Information, Economics, Control, Efficiency, and Service). The new system was designed based on the System Development Life Cycle (SDLC) methodology. Analysis results revealed several weaknesses in the current system, including low financial data accuracy, daily operational inefficiencies, and a weak internal control structure that poses risks to business continuity. As a solution, a proposed